Polarization method for determination and visualization of complex permittivity in remote sensing issues - L. Р. Ligthart; A. I. Kozlov; A. I. Logvin; I. V. Avtin (Научный вестник МГТУ ГА, 2019)
When using remote radiophysical methods in problems of monitoring the environment, the central place belongs to solving problems of determining its electrophysical characteristics, i.e. dielectric permittivity e, conductivity c (complex permittivity ek). The complex dielectric permittivity e, determined in one way or another, serves as the basis for determining the physical characteristics of the medium under study: temperature, humidity, salinity, hardness, etc. The method for remote determination of complex dielectric permittivity is proposed based on relative amplitude-phase relations in the radar receiver channels (orthogonal in polarization) (we call it determination of the polarization phasor). Knowledge of the polarization phasor makes it possible to determine uniquely both the permittivity and the conductivity of the surface under investigation. The latter is presented in the form of a series of universal graphs which allow one to directly interpret the physical characteristics of surfaces. It shows how the polarization phasor is placed on the KLL-sphere. In addition, the trajectory of the phaser on this sphere is investigated in the case when the physical characteristics of the investigated surface change. The random nature of local changes in the electrophysical properties of the surface under study leads to random fluctuations of the polarization phasor. The paper contains a two-dimensional density distribution of the permittivity and conductivity, as well as the corresponding one-dimensional densities. A graphic illustration of the relations obtained is given.